Rhynchosia mineira (Leguminosae: Papilionoideae), a new and critically endangered species from Minas Gerais, Brazil - de Paula Alves Bezerra, Luísa Maria [UNESP]; de Vargas, Wanderleia [UNESP]; Cândido, Elisa Silva; Cobra e Monteiro, Thiago [UNESP]; Vatanparast, Mohammad; Fortuna Perez, Ana Paula [UNESP] (Springer Nature, 2019)
Rhynchosia mineira is described as a new species from the state of Minas Gerais, Brazil. The taxon is morphologically similar to R. arenicola Hassl. but differs mainly in having ovate stipules, a prostrate habit, a densely pubescent stem and ovate to rhomboid leaflets. A description, illustration, distribution map, conservation status, and key to the species of Rhynchosia in the state of Minas Gerais are provided.
Keywords: Cajaninae; Phaseoleae; taxonomy